Effect of frame rate capture frequency on sperm kinematic parameters and subpopulation structure definition in boars, analysed with a CASA‐Mot system. Issue 2 (29th September 2018) - Valverde, Anthony; Madrigal, Mónica; Caldeira, Carina; Bompart, Daznia; de Murga, Javier Núñez; Arnau, Sandra; Soler, Carles
Contents: Motility is the most widely used indicator of sperm quality. Computer‐Assisted Semen Analysis (CASA) allows the objective evaluation of sperm motility parameters. CASA technology is a common tool to predict semen doses in farm animal reproduction. The kinds of video cameras used until now for image acquisition have presented limited frame rates (FR), which have a negative influence on the quality of the obtained data. The aim of the present work was to define the optimal frame rate for a correct evaluation of boar sperm motility and its subpopulation structure. Eighteen ejaculates from nine mature boars of the Pietrain breed were used. Using the ISAS ® v1 CASA‐Mot system, with a video camera working up to 200 Hz, six FRs (25, 50, 75, 100, 150 and 200 fps) were compared. ISAS ® D4C20 counting chambers, warmed to 37°C, were used. FR affected all the kinematic parameters, with curvilinear velocity (VCL) and BCF the most sensitive ones. All the parameters showed differences among animals. Non‐linear correlation showed the asymptotic level for VCL at 212 fps, being the highest FR for all the parameters. For future studies based just on progressive motility, almost 100 fps FR for 0.5 s must be used, while when kinematics must be considered, almost 212 fps for one‐second should be analysed. Three principal components were obtained (velocity, progressivity and oscillation), being similar at 50 and 200 fps. Cells were grouped in four subpopulations but with different kinematic and cellular distribution at both FRs.